Experimental Determination of a Mixture Composed of Camisea Natural Gas and CO2 Laminar Burning Velocity - Freddy Jesus Rojas; Roberto Franco Cisneros; Celso De-La-Cruz; Fernando Jimenez (Energies)
The aim of this work is to provide new experimental data on laminar burning velocities for a new synthetic mixture composed of Camisea natural gas and CO2. It was found that the relevant published experimental background data are limited to mixtures composed of methane and CO2; considering the fact that Camisea natural gas is widely used in Peru, this experimental research will serve as a supportive resource for further experimental and industrial implementations in this country, such as the design and modeling of new engines or industrial burners that are designed to be fueled by this mixture. An experimental setup for analyzing three types of flame geometry, which is feasible to implement for a wide range of conditions, was built in PUCP PI0735 laboratory and all the measurements were obtained for a range of mixtures (0%, 21.2%, 28.5%, 38.9%, 50% CO2) and ratios from around 0.55 to 0.95 at atmospheric conditions. The laminar burning velocities results obtained were analyzed in groups based on %CO2. In addition, the experimental margin error was determined by considering all the sources. The following conclusions were reached: (1) The laminar burning velocity decreases with the increase in CO2 percentage in the mixture due to the CO2 decreasing the flame temperature effect. (2) The flat flame type provided the highest value of burning velocity for each group of CO2 percentage in which it appears. (3) The highest obtained laminar burning velocity value was 22.64 ± 0.15 cm/s, for a flat flame with a ratio of 0.72 and 29.98% of CO2, while the lowest obtained value was 6.78 ± 0.15 cm/s for a conical trunk flame with a ratio of 0.59 and 49.83% of CO2. (4) The highest evaluated CO2 percentage was 50.97% for a conical trunk flame with a ratio of 0.69 and a burning velocity value of 11.04.